Analysis on Stop-hole Parameters for Fatigue Cracks at Arc Notch in Steel Bridge Deck. Issue 1 (January 2022) - Feng, Liangping; Ling, Lipeng; Meng, Cheng; Ji, Bohai
Abstract: Two types of fatigue cracks at arc notch in steel bridge deck were repaired by drilling stop-holes. The effect of stop-holes with different diameters and positions was considered. Based on finite element models, the variation laws of stress distribution and the effects of stress concentration were compared for different stop-hole diameters and positions. Analysis results indicated that stop-hole can effectively improve the stress concentration at crack tip and the fatigue life of components can be considerably increased. The crack-stopping performance enhances with the increase of stop-hole diameter, but large stop-hole cannot effectively retard crack growth. The stop-hole performs well with the location at -0.5 D ∼0.5 D . The maximum stress point still appears at crack tip when the stop-hole is outside or inside the crack. The stop-hole diameter has no effect on the stop-hole location.